LA PERVIVENCIA DE LA FÁBULA GRECO-LATINA EN LA LITERATURA ESPAÑOLA E HISPANOAMERICANA - Van Dijk, Gert-Jan (Myrtia, 2003)
In this paper the author analyzes the survival of the fable in Spanish and Southamerican Literature.